University–Industry Linkages and Graduate Skill Alignment for Regional Trade: A Meta-Analysis with Evidence from Afghanistan - Mirkhil, Farhad; Pal, Sarita (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
University–industry linkages (UIL) are widely promoted to enhance graduate employability; however, evidence from conflict-affected and fragile states remains limited. This meta-analysis synthesises empirical studies evaluating the effects of UIL on employment outcomes and labour-market alignment in Afghanistan and neighbouring South Asian countries. In accordance with PRISMA guidelines, systematic searches of Springer, ERIC, ProQuest, and Google Scholar (2014–2024) yielded 2,384 records, of which 52 studies met the inclusion criteria. Independent coders extracted study characteristics (κ = .89), and study quality was assessed using an adapted Newcastle–Ottawa Scale and the Mixed Methods Appraisal Tool (MMAT). Random-effects models indicated that graduates participating in high-UIL programmes had significantly greater odds of employment at 12 months (OR = 2.47; 95% CI, 2.03–3.01; p < .001; I² = 68.3%). Skill-job match demonstrated a large, pooled effect (d = 0.94; 95% CI, 0.73–1.16; p < .001). Additional positive effects were observed for starting salary (d = 0.68), employer satisfaction (d = 1.08), 24-month retention (OR = 1.89), and 5-year advancement (OR = 2.14). Moderator analyses identified structured internships, curriculum co-development, and institutional capacity as key mechanisms, while security context and institutional quality moderated effect sizes. Sensitivity analyses and publication bias diagnostics confirmed the robustness of the findings. Although heterogeneity and the predominance of observational designs limit causal inference, the results consistently support UIL as an effective strategy to improve graduate outcomes in fragile environments. Policy recommendations include establishing national UIL frameworks, investing in experiential learning infrastructure, and prioritising donor support for labour-market relevance.